Optimization Solid Phase Extraction of Copper(II) Using Modified Nanoporous Silica Prior to Determination by Flame Atomic Absorption Spectrometry by Taguchi Technique - Sohrabi, M.R.; Pasdar, H.; Roudbaraki, S.H.; Ghajar, S. (Asian Journal of Chemistry, 2013)
This paper deals with solid phase extraction coupled with atomic absorption spectrometry for determination of Cu(II) in trace level in aqueous solution. Design of experiment, based on Taguchi technique, is used to evaluate optimum conditions of separation. Design of experiment approach is a method to reduce the time and onus of experiments in comparison with one factor at a time optimization. For experimental parameters pH, flow rate, time and absorbent dosage were applied at three levels to achieve suitable conditions of separation of Cu(II). Results indicate that flow rate parameter, at low level and time parameter, at high level, are more effective than other parameters at the best separation of Cu(II) which is equal to 96.3 %.